(untitled) - Pfister, Joel (Chapel Hill, 1995)
Staging Depth undertakes something radically new in the study Eugene O'Neill: an interpretation of his works from the perspective of the fictions that substained them. formal experimentation and thematic obsession make up the usual stuff of O'Neill criticism, but Joel Pfister seeks to breakthat conventional mold....
Keywords: Literature and society,Domestic drama, American,Drama,Middle class in literature,Psychology in literature,Families in literature,Văn học và Xã hội,Tâm lý trong văn học; History,History and criticism,Psychological aspects,Lịch sử; 20th century,Thế kỉ 20; United States,Mỹ